Kontribusi Harapan Orang Tua terhadap Kecenderungan Stres Akademik Siswa Kelas XII SMA Negeri di Kota Padang - Yanra, Metrilani (Lembaga Yasin AlSys, 2024)
The purpose of this study was to determine the Contribution of Parental Expectations to the Tendency of Academic Stress of Class XII State High School Students in Padang City. Data were collected with the Parental Expectations Scale and Academic Stress from 259 samples. Sample selection using propotional random sampling technique. Data analysis used is simple linear regression analysis. With the results of p value = 0.000 (p <0.05). This shows that there is a Contribution of Parental Expectations to Academic Stress of Class XII High School Students in Padang City. The coefficient of determination (R2) = 0.068, this shows that parental expectations have a contribution of 6.8% to academic stress. The constant value obtained is 49.831. it can be interpreted that if parental expectations are worth 0 (constant), then academic stress is worth 49.733. The regression coefficient value of the parental expectations variable is positive (+) of 0.297, it means that, if parental expectations increase, academic stress will increase, and vice versa.